Mitral repair best practice: proposed standards. Issue 7 (26th October 2005) - Bridgewater, B; Hooper, T; Munsch, C; Hunter, S; von Oppell, U; Livesey, S; Keogh, B; Wells, F; Patrick, M; Kneeshaw, J; Chambers, J; Masani, N; et al.
Abstract : Objectives: To define best practice standards for mitral valve repair surgery. Design: Development of standards for process and outcome by consensus. Setting: Multidisciplinary panel of surgeons, anaesthetists, and cardiologists with interests and expertise in caring for patients with severe mitral regurgitation. Main outcome measures: Standards for best practice were defined including the full spectrum of multidisciplinary aspects of care. Results: 19 criteria for best practice were defined including recommendations on surgical training, intraoperative transoesophageal echocardiography, surgery for atrial fibrillation, audit, and cardiology and imaging issues. Conclusions: Standards for best practice in mitral valve repair were defined by multidisciplinary consensus. This study gives centres undertaking mitral valve repair an opportunity to benchmark their care against agreed standards that are challenging but achievable. Working towards these standards should act as a stimulus towards improvements in care.